Effectiveness of Myofascial Release on Mouth Opening in Subjects with Post Operative Buccal Mucosa Carcinoma. - Sekar, Madhanraj; Kumaresan A.; Srinivasan, Vignesh; Vishnuram, Surya; kumar, Priyadharshini; Alagesan, Jagatheesan (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Patient treatment after surgical excision of buccal mucosal carcinoma should prioritise symptom relief and cancer prevention. Mouth exercise physiotherapy is widely regarded as a staple for expanding the mouth, either on its own or in conjunction with other modalities. In order to better understand the manufacture and clinical effectiveness of Triscare mouth exercising devices in subjects with CA buccal mucosa, the current study was conducted. Purpose: This study aims to evaluate the effectiveness of Myofascial release for postoperative buccal cancer patients. Materials and Methods: Subjects with buccal mucosa carcinoma were recruited from Saveetha Dental College and Hospital for an experimental research using inclusion and exclusion criteria. Two week postoperative Buccal Mucosa Carcinoma subject volunteer. The participants were secretly separated into two groups using envelopes. Before and after treatment, jaw exercise and Myofascial release groups had their mouth opening and quality of life evaluated. Statistical analysis was performed on the collected data, and conclusions were drawn. Results: At the 4-week follow-up, the intervention group's mean MO (48.06mm) was significantly higher than the control group's (44.66 mm) (p 0.002), and the intervention group also reported significantly higher GTQ scores and higher health-related quality of life scores across all domains and items. Conclusion: We concluded that Participants in the intervention group improved more than those in the control group, and they also reported higher levels of engagement with and satisfaction with their therapy.